The orchid-bee faunas (Hymenoptera: Apidae) of 'Parque Nacional do Monte Pascoal', 'Parque Nacional do Descobrimento' and three other Atlantic Forest remnants in southern Bahia, eastern Brazil - Nemésio,A (2013)
The orchid-bee faunas of ‘Parque Nacional do Monte Pascoal’, ‘Parque Nacional do Descobrimento’ and three other Atlantic Forest remnants ranging from 1 to 300 ha in southern Bahia, eastern Brazil, were surveyed. Baits with seventeen different scents were used to attract orchid-bee males. Four thousand seven hundred and sixty-four males belonging to 36 species were actively collected with insect nets during 300 hours from November, 2008 to November, 2009. Richness and diversity of orchid bees found in this study are the highest ever recorded in the Atlantic Forest domain. Eufriesea dentilabris (Mocsáry, 1897) and Eufriesea violacea (Blanchard, 1840) were collected at the ‘Parque Nacional do Monte Pascoal’, the first record of these species for the state of Bahia and the northernmost record for both species. Females Exaerete dentata (Linnaeus, 1758) were also collected at ‘Parque Nacional do Monte Pascoal’ and old records of Eufriesea aeneiventris (Mocsáry, 1896) in this area makes this site the richest and most diverse concerning its orchid-bee fauna in the entire Atlantic Forest and similar to areas in the Amazon Basin.